Most Noble Part of the Empire: The Image of Italy and Sicily in the XI Century Byzantine Historiography - Samčević, Vuk R. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
This paper aims to show how 11th-century Byzantine historians viewed Italy and Sicily during a specific period when the Empire lost all its possessions in these provinces. By analysing the histories of Michael Psellus, Cecaumenus, Michael Attaliates, John Scylitzes, and Scylitzes Continuatus, we explore their portrayal of the loss of these provinces, which were historically closely linked to Ancient Roman history. After presenting Byzantine Italy and Sicily in the 11th century, the paper discusses the image of Italy as the birthplace of Ancient Rome and references to the distant past of Italy and Sicily found in the texts under review. Special emphasis is placed on the importance of Italy and Sicily for these historians, examining possible differences in their presentation of the provinces and the reasons behind them. In the final part, the paper analyses how anecdotes in the histories can offer valuable information on the understanding of these regions and their place in Byzantine collective memory.